2017
DOI: 10.3389/fphys.2017.00235
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 in the Lateral Parabrachial Nucleus Inhibits Food Intake, Modulates Excitability of Glucosensing Neurons, and Enhances UCP1 Expression in Brown Adipose Tissue

Abstract: Nesfatin-1, an 82-amino acid neuropeptide, has been shown to induce anorexia and energy expenditure. Food intake is decreased in ad libitum-fed rats following injections of nesfatin-1 into the lateral, third, or fourth ventricles of the brain. Although the lateral parabrachial nucleus (LPBN) is a key regulator of feeding behavior and thermogenesis, the role of nesfatin-1 in this structure has not yet been delineated. We found that intra-LPBN microinjections of nesfatin-1 significantly reduced nocturnal cumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…These observations, together with the present data, suggest that nesfatin-1, when given acutely, may affect responsiveness to UCP1 rather than its production. This view is supported by another recent study showing that UCP1 protein levels are significantly increased upon a 5-day site-specific central application of nesfatin-1 [27]. Alternatively, the time-window at which the UCP1 mRNA was increased may have simply been overlooked.…”
Section: Discussionmentioning
confidence: 85%
“…These observations, together with the present data, suggest that nesfatin-1, when given acutely, may affect responsiveness to UCP1 rather than its production. This view is supported by another recent study showing that UCP1 protein levels are significantly increased upon a 5-day site-specific central application of nesfatin-1 [27]. Alternatively, the time-window at which the UCP1 mRNA was increased may have simply been overlooked.…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, ICV injected nesfatin-1 30–59 , described as the active core of nesfatin-1 [ 2 ], increased satiety as well whereas satiation was not altered in mice [ 32 ], giving rise to differential receptor binding or activation. Lastly, in rats nesfatin-1 30–59 induced satiation but not satiety [ 33 ], pointing toward species differences, a finding confirmed after microinjection of nesfatin-1 into the lateral parabrachial nucleus in rats [ 34 ]. Although the effect of nesfatin-1 30–59 was retained during diet-induced obesity (DIO) in rats [ 33 ], giving rise to a leptin-independent signaling as suggested before [ 1 , 2 ], the underlying microstructure differed, with increased satiety [ 33 ] suggesting different downstream signaling under conditions of obesity.…”
Section: Implications Of Nesfatin-1 In the Regulation Of Food Intamentioning
confidence: 94%
“…This finding was also confirmed in chicks with astressin-B, a CRF 1/2 antagonist [ 35 ]. Because the melanocortin receptor 3/4 antagonist SHU9119, with anorexigenic melanocortin 4 signaling being well established upstream of CRF [ 36 , 37 ], attenuated [ 34 ] or blocked [ 1 ] nesfatin-1’s anorexigenic effect, nesfatin-1 might act via melanocortin → CRF signaling to inhibit food intake.…”
Section: Implications Of Nesfatin-1 In the Regulation Of Food Intamentioning
confidence: 99%
“…Nevertheless, UCP1 protein levels could be affected at a different time-point. Of note, a recent study showed that subchronic central nesfatin-1 treatment resulted in increased UCP1 protein levels (Yuan et al 2017).…”
Section: :2mentioning
confidence: 99%